Pancreatic pseudo-cyst. - José Raúl Sánchez Aguilar; Neyda Delgado Marín; Jalima Jiménez Morejón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
The pancreatic pseudocyst is the most common cystic lesion of the pancreas. It constitutes an amilasa rich liquid collection, located inside or adjacent to the pancreas; surrounded by a wall without ephithelium, as result of a sharp or chronic pancreatitis, pancreatic trauma, or obstruction of pancreatic conduit. 50 % solves spontaneously in 6 weeks, but some of they require surgical treatment. We presented the Good Clinical Practices Guideline for Pancreatic pseudocysts, approved by consent in the 3th National Good Clinical Practices Workshop in Pediatric Surgery (Camagüey, Cuba; February 23 - 26, 2004).